2021
DOI: 10.3389/fnrgo.2021.749009
|View full text |Cite
|
Sign up to set email alerts
|

Brain Synchrony in Competition and Collaboration During Multiuser Neurofeedback-Based Gaming

Abstract: EEG hyperscanning during multiuser gaming offers opportunities to study brain characteristics of social interaction under various paradigms. In this study, we aimed to characterize neural signatures and phase-based functional connectivity patterns of gaming strategies during collaborative and competitive alpha neurofeedback games. Twenty pairs of participants with no close relationship took part in three sessions of collaborative or competitive multiuser neurofeedback (NF), with identical graphical user interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…Our final research question concerns the existence of interbrain connectivity. In our previous study, we showed that during competitive gaming, the PLV was asymmetricalalmost all cortical areas in W players were in synchrony with the parietal area of L players in the alpha band (Susnoschi Luca et al, 2021). Because PLV is non-directional, the method could not reveal the direction of information flow.…”
Section: Interbrain Connectivitymentioning
confidence: 98%
See 3 more Smart Citations
“…Our final research question concerns the existence of interbrain connectivity. In our previous study, we showed that during competitive gaming, the PLV was asymmetricalalmost all cortical areas in W players were in synchrony with the parietal area of L players in the alpha band (Susnoschi Luca et al, 2021). Because PLV is non-directional, the method could not reveal the direction of information flow.…”
Section: Interbrain Connectivitymentioning
confidence: 98%
“…Interaction between BCI players includes working towards a common goal (collaboration) or working individually to assert dominance (competition). Collaborative gaming has been based on different BCI modalities, such as steady-state visual evoked potential (Li and Nam, 2016), event-related potential (Poli et al, 2014), P300 (Korczowski et al, 2015), motor imagery (MI) (Bonnet et al, 2013), and operant conditioning (Hjelm & Browall, 2000;Susnoschi Luca et al, 2021). Collaboratively performing a task has the potential to improve players' performance (Y.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have examined these questions using dyadic neurofeedback paradigms, in which participants' brain activity is visualized (e.g., by displaying coherence metrics between two people's EEG readings; Chen et al, 2021), allowing them to see whether it is synchronized or not. Participants who are instructed to use this feedback to increase their inter-brain synchrony over time are able to do so (e.g., Susnoschi Luca et al, 2021). Dyadic neurofeedback studies in humans (Müller et al, 2021) and in pigeons (Yang et al, 2020) have demonstrated causal links between inter-brain synchrony and prosociality; the researchers increased inter-brain synchrony using dyadic neurofeedback and demonstrated that this increased synchrony was associated with more pro-social experiences (Müller et al, 2021) and behavior (Yang et al, 2020).…”
Section: Inter-brain Synchrony Relationships and Therapeutic Alliancementioning
confidence: 99%